A Theory of Sales Quotas with Limited Liability and Rent Sharing - Oyer, Paul (Journal of Labor Economics, 2000)
Sales quotas are a fixture of sales compensation plans and are often associated with a significant discrete bonus. This article shows that, under certain assumptions about salesperson utility and the distribution of sales outcomes, the optimal compensation is a discrete bonus for meeting a sales quota. The results are similar when the assumption of agent risk neutrality is relaxed. The model has implications for many moral hazard problems where the agent has a liability limitation and job‐specific skill.